2007
DOI: 10.1007/s00535-007-2082-4
|View full text |Cite
|
Sign up to set email alerts
|

Coexistence of gastrointestinal stromal tumors with other neoplasms

Abstract: In almost 27% of the study population, GISTs coexisted with other neoplasms. A greater proportion of patients with a GIST localized in the small intestine and/or characterized by a very low risk of aggressive behavior and accompanying other neoplasms, compared with a GIST alone, most likely reflects the fact that in the first group, GISTs tended to be an incidental finding during surgery. The results were affected by patient selection and the type of tissue material available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
59
1
15

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(83 citation statements)
references
References 63 publications
5
59
1
15
Order By: Relevance
“…Contrary to the majority of previous cases of synchronous GISTs and other malignancies (9,10), and the other case report of synchronous GIST and pancreatic adenocarcinoma (8), in our case, GIST was not an incidental finding. Our initial impression was a symptomatic GIST; however, following reevaluation via a CT scan with a multidisciplinary approach, a pancreatic adenocarcinoma was suspected.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Contrary to the majority of previous cases of synchronous GISTs and other malignancies (9,10), and the other case report of synchronous GIST and pancreatic adenocarcinoma (8), in our case, GIST was not an incidental finding. Our initial impression was a symptomatic GIST; however, following reevaluation via a CT scan with a multidisciplinary approach, a pancreatic adenocarcinoma was suspected.…”
Section: Discussioncontrasting
confidence: 99%
“…Agaimy and Wuensch analyzed a series of 97 cases of surgically resected GIST and revealed that the majority of GISTs in their series were benign or low-risk and appeared to be innocent bystanders (2). Liszka et al identified that these GISTs tended to be an incidental findings during surgery, and were most commonly localized in the small intestine (10). In our case, the GIST was associated with an intermediate risk and located in the stomach.…”
Section: Discussionsupporting
confidence: 45%
“…Liszka et al [6] reported that during this association, the stromal tumor is generally small in size, often less than 2 cm and presents a low risk of invasion and recidivism compared to isolated GIST, with a mitotic index often less than 5 and a Ki-67 less than 5% [4], suggesting a probable inhibition of the malignancy of the stromal tumor by adenocarcinoma.…”
Section: Discussionmentioning
confidence: 97%
“…Według klasyfikacji Laurena wyróżnia się typ jelitowy (I), rozlany (II) oraz mieszany (III). Guzy stromalne (gastrointestinal stromal tumor -GIST) oraz raki endokrynne żołądka są znacznie rzadsze, pomimo iż 60% GIST zlokalizowanych jest w żołądku [1][2][3][4][5][6][7][8][9][10]. W niniejszej publikacji autorzy przedstawiają bardzo rzadką sytuację, w której stwierdzono trzy różne typy histologiczne współistniejących ze sobą guzów w jednym narządzie [1][2][3][4][5][6][7][8][9][10].…”
Section: Wstępunclassified